Concentrations of trace elements measured in lichens and soils at Lhù'ààn Mân' (Kluane Lake, Yukon Territory, Canada) in August 2021 - Pouille, Sophie (PANGAEA, 2024)
We observed increased trace element concentrations in lichens and soils at sites closer to the dust source. Vegetation was more impacted by dust deposition, as well as the 0-2 cm soil layer compared to the 2-10 soil layer. The parameters measured were nickel (Ni) (mg/kg), copper (Cu) (mg/kg), arsenic (As) (mg/kg), cadmium (Cd) (mg/kg), lead (Pb) (mg/kg), total carbon (C) (%), total nitrogen (N) (%), total phosphorus (P) (mg/kg), CN ratio and pH in lichens and soils, manganese (Mn) (mg/kg), magnesium (Mg) (mg/kg), potassium (K) (mg/kg), aluminum (Al) (mg/kg), calcium (Ca) (mg/kg), iron (Fe) (mg/kg), sodium (Na) (mg/kg) in soils, tree, shrub, herb, moss and lichen cover (%). Terricolous lichen Peltigera canina was sampled with a stainless-steel knife and scissors in three replicas at 53 sites within 10 km of the delta, and 4 control sites at 11 and 30 km. Sampling sites were located near the roads for accessibility reasons, but the sampling was done at least 100 m from the road to lessen the influence of the road itself. Two layers were sampled, one at 0-2 cm and the other one at 2-10 cm in three replicas at each site with a stainless trowel. Lichen samples were digested in 2 mL of HNO3, and soil samples in 4 mL of HNO3 and 1 mL of HCl. Trace elements (Ni, Cu, As, Cd, Pb) were determined in lichens and soils, and minor elements (Al, Ca, Fe, K, Mg, Mn, and Na) in soils by Inductively coupled plasma mass spectrometry (ICP-MS; PerkinElmer NexION 300x, PerkinElmer Syngistix). Total carbon and nitrogen concentrations were analyzed by CHNO-S elemental analysis, Fisons - EA-1108 CHNS-O Element Analyzer. Total P content was analyzed using Shimadzu UV spectrophotometry. The pH was analyzed with a pH meter Fisher Accumet pH Meter AB 150. The percent cover of vegetation layer (tree, shrub, herb, moss, and lichen) was characterized within a 20-meter radius around the central point of each sampling site. We followed the inventory method recommended by the Field Manual for Describing Terrestrial Ecosystems (Erwin, 2010), which is used by the territory (Environment Yukon, 2016, 2017). The data was collected in the field in August 2021 and the analyses were performed between September 2021 and February 2022. The temporal coverage is yearly. The data collection was done at Lhù'ààn Mân' (Kluane Lake), Yukon Territory, Canada. The geographical coverage is regional. The dataset covers 33 km with 57 sites. The data was collected to understand the impacts of dust deposition on high latitudes ecosystems. Specifically, the purpose of this study was to determine the impacts of dust deposition on trace element concentrations in lichens and soils, to further elucidate the implications for vegetation and soil properties within subarctic ecosystems. The dataset can be used to compare to other trace element concentrations from other sources like anthropogenic activities, but the trace element concentrations measured at Lhù'ààn Mân' are low compared to trace element concentrations usually reported for anthropogenic sources.
Keywords: dust; lichens; Soil; subarctic; trace elements; yukon